Diet, Knowledge and Hypertension : a Correlation Study for Elderly with Hypertension - Gusti Nurul Husna; Irfan Baharuddin Pakki; Akhmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Healthy dietary behavior is one of the key factors in maintaining nutritional status and preventing degenerative diseases, particularly among the elderly population. Hypertension is one of the most prevalent chronic health problems experienced by older adults. The prevalence of hypertension in the elderly tends to increase with age and is mostly associated with unhealthy lifestyle behaviors, especially dietary patterns that do not follow the principles of a hypertension diet. Objective : to analyze the correlation between knowledge and healthy lifestyle patterns in elderly people with hypertension Research Methods/ Implementation Methods : This study employed a cross-sectional design. The sample consisted of 100 respondents aged 60–65 years selected using purposive sampling in the Bengkuring Public Health Center. Data were collected through questionnaires covering respondent characteristics, knowledge level, and dietary behavior. The data were analyzed using the Spearman correlation test with a significance level of 0.05. Results : The results showed that out of the five dietary behavior components observed, only one component showed a significant correlation between knowledge and lifestyle behavior related to caffeine and smoking consumption, with a p-value of 0.011 (<0.05). Elderly individuals who possess better knowledge regarding the effects of caffeine and smoking on hypertension tend to be more cautious in consuming these substances. Cigarettes and caffeine are known to increase sympathetic nervous system activity and elevate blood pressure. Conclusion/Lesson Learned : Knowledge have an important yet limited role in shaping healthy lifestyle behaviors among elderly individuals with hypertension.